OPTICAL BAND GAP ANALYSIS OF NANO-CRYSTALLINE CERAMIC PbSrCaCuO - Isac, Jayakumari (JOURNAL OF ADVANCES IN PHYSICS, 2014)
ABSTRACT Nano-crystalline Ceramic PbSrCaCuO have been prepared by a high-energy ball milling process through mechanically assisted synthesis. The prepared sample was then subjected to calcinations to acquire the desired homogeneity and phase formation. UV-VIS analysis of the sample was carried to study the optical properties of the sample. The band gap energy of the sample shows a marked variation in their value with the increase in temperature. The refractive index n was calculated andÂ  the results obtained is plottedÂ  with the wavelength. The refractive-index curves also show a systematic variation with temperature.